Funnctional Thinking Processes of Maritime Vocational Students with and without GeoGebra - Luthfiana Tarida; Dedeh Suryani (Indonesian Journal of Mathematics Education, 2026)
Functional thinking has been recognized as an important mathematical competence for maritime students because it can support the understanding of relationships among variables involved in navigation and shipping safety. However, research examining how this competence develops through mathematical problem-solving, particularly with and without the support of dynamic technology in vocational higher education, remains limited. This study investigated differences in the functional thinking processes of maritime students when solving mathematical problems with and without GeoGebra. This study employed a qualitative comparative design involving two participants from the Nautical Study Program who were purposively selected based on their relatively homogeneous mathematical ability, as indicated by the smallest difference in their mathematics test scores. Both participants completed non-routine linear interpolation tasks followed by task-based interviews. Data were analyzed comparatively based on aspects of functional thinking. Both participants were able to identify and represent the relationship between cargo space height and cargo capacity. Differences were observed in the extent to which they generalized and evaluated this relationship. The findings provide preliminary evidence that different representational environments may be associated with distinct pathways of functional thinking. This study contributes to the limited body of research on functional thinking in maritime vocational education by providing an initial description of students’ reasoning processes and by highlighting the potential of GeoGebra as a dynamic representational tool for exploring functional relationships in authentic maritime contexts.